ANALISIS FINANCIAL DISTRESS MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN ASURANSI YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2011 – 2014 - Setyaningsih Sri Utami, Icha Cahyaningtyas, Untung Sriwidodo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aims to determine the financial condition of insurane companies listed on the Indonesia Stock Exchange from 2011-2014. By using the Altman Z-Score to see how much financial distress on the insurance companies, amounting to 9companies.By using the formula Z-Score = 1,2 X1+1,4 X2+3,3 X3+0,6 X4+1,0 X5. The results showed a total of 9 insurance companies that went public there are still some who are greeting bankrupt condition. In 2011, as many as 22,2% of companies declared bankrupt, 77,9% gray area, and 0% declared healthy. In 2012, as many as 55,6% of companies is declared bankrupt, 44,4% gray area, and 0% declared healthy. In 2013, as many as 44,4% of companies is declared bankrupt, 55,6% gray area, and 0% declared healthy. In 2014, as many as 55,6% of companies was declared bankrupt, 44,4% gray area, and 0% declared healthy.Keywords: altman z-score, financial distress